La situación de los incendios en el Valle del Tiétar - Cepeda Serna, Cristina; García Quiroga, Fernando; Abad Soria, Jesús (Observatorio Medioambiental, 2007)
The Valley of the Tiétar (Ávila) it is one of the spaces inside the peninsular geography that shows a bigger number of forest fires. The topographical and climatic conditions, next to an inadequate politics of reforestations and other more recent threats as the development urbanístico and of new infrastructures for the transport, they are the biggest problems to those that it faces this space considered by many as an ecological treasure. It demonstrates it to it being declared as Area of Special Protection for the Ave (ZEPA) and I eat Place of Community Interest (LIC).